On the Road to Equity: Examining Income-Related Inequalities in Ownership of Safer Vehicles - Vincenzo Carrieri; Apostolos Davillas; Victor Hugo de Oliveira (Institute of Labor Economics (IZA), 2023)
Using administrative DVLA data matched with micro-data from Understanding Society – the UK Household Longitudinal Study we estimate income-related inequalities in ownership of vehicles with a set of safety features and we apply a regression-based decomposition method for rank-dependent inequality measures to estimate the source of inequalities. We find systematic pro-rich inequalities in ownership of passively safer vehicles that are almost entirely explained by the characteristics of the vehicles, mainly their price and year of manufacture. A wide range of variables measured at the household level including demographics, risk aversion and time preference proxies, personality traits, cognitive ability, and education plays a much less pronounced and, in most cases, non-statistically significant contribution to overall inequality. These findings reveal inequity in access to passively safer vehicles with potential effects on the socio-economic gap in road-traffic injuries and mortality rates, requiring regulatory intervention.
Keywords: I10; I14; R41; 330; income inequalities; car's safety; concentration indexes; United Kingdom